Assessment of Aortic Stenosis Severity by Cardiovascular Magnetic Resonance - García., J.; Markl., M.; Barker., A. J. (Revista Mexicana de Ingenieria Biomedica, 2013)
Cardiovascular magnetic resonance (CMR) has become a valuable tool to corroborate aortic stenosis (AS) severity when echocardiography assessment is discordant. Moreover, CMR can provide useful complementary information about AS severity and hemodynamic markers. In particular, the use of advanced 4D flow CMR allows a comprehensive assessment of complex flow alterations produced by AS. This review provides an overview of the added value obtained by standard 2D flow and advanced 4D flow quantification for AS severity assessment and discusses the advantages and disadvantages of current clinical metrics. This includes an introduction of promising new hemodynamic markers, and discusses how these novel makers may identify